Risiko Paparan Benzena Terhadap Kandungan Fenol Dalam Urin Pekerja Pengecatan Mobil Di Kecamatan Tampan Kota Pekanbaru Tahun 2017 - Darnita Darwis; Mubarak Mubarak; Sofia Anita (Universitas Riau, 2018)
Benzene is well known as a good organic solvent for various processes in industry such as rubber industry, shoes, paint solvents and others. Benzene is a chemical that has long been known to be dangerous to human health because of carcinogenic. One of the informal sectors exposed to benzene is a car painting workshop. This study is intended to determine the levels of phenol in workers urine and analyze the effects of the exposureon the characteristics of the car painting worker in sub districts of Tampan Pekanbaru. The methods used in study are survey and interview. The analysis used in this research is a multiple linear regression, where the independent variable more than 2 variables. They are smoking habit, length of work, duration of exposure and use of PPE. The examination by using the UV-Vis spectrophotometer apparatus. The result showed that were 6 workers who had phenolythuramines level above 20 mg/L exceed of WHO standards. The analysis result found that is affect workers characteristic which is significant to the phenol level in workers urine that has exposed to the benzene.